2010
DOI: 10.1590/s0103-84782010005000093
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência e distribuição espacial e temporal do coleóptero Naupactus curtus em cafeeiros de Minas Gerais, Brasil

Abstract: III Ocorrência e distribuição espacial e temporal do coleóptero

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…Dentre os fatores causadores de perdas na produtividade da cebola estão as pragas e doenças. Alguns insetos que não eram pragas e restritos a poucas áreas no Brasil são hoje importantes pragas, causando prejuízos consideráveis para a agricultura do país (Fernandes et al 2010).…”
Section: _____________________________________unclassified
“…Dentre os fatores causadores de perdas na produtividade da cebola estão as pragas e doenças. Alguns insetos que não eram pragas e restritos a poucas áreas no Brasil são hoje importantes pragas, causando prejuízos consideráveis para a agricultura do país (Fernandes et al 2010).…”
Section: _____________________________________unclassified
“…al., 1996;Awadalla, 1997;Abou-Attia, 1999;Bazazo, 2005 andFatma H. Hegazy andEl-Sheikh, 2021) Formicid species are very effective biocontrol agents for several reasons; colonies contain large numbers of individuals that consume large populations of prey and their predation is not limited to a particular prey species or stage (Paulson and Burts, 1993). As well, in many countries, several studies have demonstrated that ants can be key generalist predators of crop pests (El-Keroumi et al, 2010;Fernandes et al, 2010 andSanders &Van Veem, 2011). Wu et al, (2013) and Chandish and Verghese (2015), demonstrated that formicid species are important predators of Lepidoptera eggs and larvae.…”
Section: Introductionmentioning
confidence: 99%